Clinical Manifestations of Adult Langerhans Cell Histiocytosis with Multisystem Involvement Successfully Treated Using Chemotherapy - Nai-Yu Lin; Xu-Hua Tang; Jian-De Han (Wolters Kluwer Health, 2021)
Abstract. Introduction:. Langerhans cell histiocytosis (LCH), the most common histiocytic disorder, characterized by the abnormal over production of histiocytes that tend to infiltrate single or multiple organ systems leading to significant tissue damage. Here we report a case of an adult patient who was diagnosed with LCH presenting as multisystem involvement. Case presentation:. We describe a 23-year-old man suffering from central diabetes insipidus, "hemorrhoids", progressive hearing loss and a surge in weight. Physical examination revealed lesion involvement of the skin and mucous membranes, including the perianal area, gingiva, and external auditory canal. He was diagnosed as LCH, who achieved remission following a chemotherapy regimen. Discussion:. LCH is common in children, but it is not surprising to see it in adults. The clinical manifestations of LCH are highly variable and may involve multiple organs and systems. While, skin involvement is the most obvious symptom, and dermatologists should be familiar with it. Chemotherapy is the first-line treatment for multisystem or multifocal single system adult LCH. Conclusion:. Characteristic features of LCH involving the perianal area was described in this case which helped the dermatologist to make quick judgments. We also emphasize that a global concept should be established confronting with a patient with multiple complaints.